A Woman with Rheumatoid Arthritis and a Bilateral Fracture of the Proximal Tibia - J. Th. (Arjan) Hooghof; Joris J. Mellema; Marcel D. Posthumus; Jos J. A. M. van Raaij (Case Reports in Orthopedics)
A 52-year-old woman presented herself with pain on the medial sides of the proximal tibia after a minimal trauma. Conventional X-rays did not show any pathology. However, the MRI showed a bilateral fracture of the proximal tibia. Since the patient was treated with methotrexate due to rheumatoid arthritis, methotrexate osteopathy was considered. Long term treatment with low doses of methotrexate proved to inhibit osteoblast proliferation and may eventually lead to decreased bone formation and osteopenia. On the other hand, immobilization, joint deformities, and steroid treatment are associated with rheumatoid arthritis and are also known risk factors for fractures. The clinical relevance of methotrexate osteopathy still has to be established. However, if a patient treated with methotrexate localizes pain in the tibia, methotrexate osteopathy should be considered. Withdrawal of the drug may improve symptoms.